Evaluation And Optimization Strategy Of Regional Asset Management In The General Bureau Of The Asset Division Of The Governor's Office Of North Sumatera Province - Fitri Auditya Utami; Rulianda Purnomo Wibowo; Emerson Pascawira Sinulingga (Universitas Muhammadiyah Tapanuli Selatan, 2026)
Regional Asset Management (BMD) is a crucial aspect in supporting accountable, transparent, and effective governance. However, asset management at the General Bureau of the Asset Section of the North Sumatra Provincial Governor's Office still faces several challenges, such as inconsistencies in asset data, late recording, suboptimal inventory, and weak internal controls. These conditions indicate a gap between current asset management practices and the ideal conditions according to applicable regulations. This study aims to identify the actual condition of asset management, evaluate its level of optimization, analyze the gap between actual and ideal conditions, and formulate an asset management optimization strategy. The study used a qualitative descriptive approach, collecting data through interviews, observation, documentation, and questionnaires with nine respondents. Data analysis was conducted using a gap analysis approach. The results indicate that asset management has been running quite well, but is not optimal in terms of data accuracy, recording, inventory, supervision, and utilization of information technology. The gap analysis indicates that there are still differences between the actual and ideal conditions of asset management. Therefore, an optimization strategy was formulated through strengthening the asset management system, improving inventory quality, strengthening internal controls, enhancing human resource competency, and optimizing the use of information technology. This strategy is expected to increase the effectiveness of asset management, orderly administration, and accountability in the management of Regional Property.